Effects of Health Education on Leptospirosis Prevention Through Dasawisma - Sri Mulyanti; Athanasia Budi Astuti (Jurnal Ners, 2018)
Introduction: Globally, leptospirosis is still a major health problem in African and developing countries, including Indonesia. The best control effort is with prevention through health education. Health education with conventional methods is considered less effective, so there is a need to look for other health education methods.Methods: Aims of the research are to know the difference of effectiveness of health education methods between conventional classical method and dasawisma or peer group in (1) improvement of knowledge of leptospirosis disease prevention; (2) effectiveness in prevention of leptospirosis. Research is Quasi-Experimental research with a two-group control trial design. The sample consisted of 40 respondents treated by health education through dasawisma using a leptospirosis module as a media of Health Education, and 40 control group respondents who were given education using conventional method. Sampling technique used purposive sampling. Data were statistically analyzed with Independent T-Test.Results: (1) Meaning of treatment group = 21.77 higher than control group = 19.62 (2) Mean prevention effort of leptospirosis disease treatment group = 54.35 better than control group = 48.15 (3) Health education through dasawisma was effective to increase knowledge prevention of leptospirosis (t = 2.943; p = 0.004) (4) Health education through dasawisma was effective for increasing prevention effort of leptospirosis (t=4.695; p=0.001).Conclusion: Health education through dasawisma and leptospirosis module is significantly effective to improve knowledge of leptospirosis disease and in prevention efforts of leptospirosis.